Kinerja NU Care-Lazis NU Desa Sugihan dalam Mengelola dan Mendistribusikan Infak dan Sedekah: Studi Dampak terhadap Kesejahteraan Masyarakat di Desa Sugihan, Kecamatan Jatirogo, Kabupaten Tuban - Muttaqin, Zainal; Arifah, Cinthiya Zakiah (Program Studi Ekonomi Syariah STAI Senori Tuban, 2024)
This research aims to discuss the performance of NU CARE-LAZIS NU Sugihan Village in managing and distributing infaq and alms: a study of the impact on community welfare in Sugihan Village, Jatirogo District, Tuban Regency. This research uses a qualitative approach, which aims to understand in depth the process of managing and distributing infaq and alms by NU CARE-LAZIS NU Sugihan Village. Data collection techniques include interviews, observation, and documentation. The research results show that (1) NU Care-LAZIS NU is a village-level philanthropic institution in Sugihan Village, which has been established since 2019, (2) the performance of the NU Care-LAZIS NU management in Sugihan Village, has succeeded in managing and distributing donations as well as alms per the planned work program, (3) the program run by NU Care-LAZIS NU Sugihan Village has provided various positive impacts aimed at improving community welfare. The program includes conditional assistance, monthly programs, and annual programs, (4) NU Care-LAZIS NU Sugihan Village provides real benefits for the community and helps improve welfare, but there are still challenges in its realization, such as manual administration, negative perceptions of some residents, limitations delivery personnel, protests regarding the type of aid, and high public expectations. Even though there are differences of opinion within the management, this can be resolved with mutual respect.